Economic Impact and Adoption Barriers of Drone Technology in Indian Paddy Cultivation - Malaisamy A; Gowri Shankar R; Raswanthkrishna M (Current Research Progress in Agricultural Sciences Vol. 8, 2025)
Agriculture remains the backbone of India’s economy, with nearly 47 percent of the population relying on it for their livelihood. Indian agriculture is the backbone of the nation, feeding over 1.4 billion people and employing nearly half of the population. Yet, it grapples with mounting challenges—declining productivity, labor shortages, outdated practices, and climate-induced uncertainties. Paddy cultivation, a staple crop for millions, remains heavily reliant on labor-intensive methods that limit efficiency and profitability. Enter drone technology—an innovation poised to transform the agricultural landscape. Drones, equipped with advanced sensors and imaging capabilities, are revolutionizing farming by providing real-time insights into crop health, soil conditions, and pest infestations. This precision-driven approach empowers farmers to optimize water, fertilizers, and pesticides, ensuring maximum yield with minimal waste. Our study, conducted in Tamil Nadu, unveils the staggering economic benefits of drone-assisted paddy farming. The results are striking—economic efficiency surges by 90%, cultivation costs drop by 30%, and farmer incomes soar by an impressive 41%. These gains stem from targeted interventions, reduced resource wastage, and healthier crops that withstand pests and diseases more effectively. By shifting from conventional farming to drone-powered precision agriculture, farmers can secure higher yields, superior produce quality, and greater financial stability. Despite its game-changing potential, drone adoption in India faces hurdles—high initial costs, limited technical know-how, and regulatory constraints. Overcoming these barriers through supportive policies, subsidies, and farmer training programs is crucial to unlocking the full potential of this cutting-edge technology. The future of Indian agriculture lies in innovation, and drones are at the forefront of this transformation.